(untitled) (Foro de Educacion, 2015)
Modern Western states have a history of the thinking tradition, where the development of human societies is seen as independent from ecological constraints. Our thinking is a social construction, a product of the human mind. It can be changed. In this article we describe a new approach to well-being called an Ecosocial Approach to Well-Being (EAW). It is a holistic and multidisciplinary approach to well-being that will facilitate the analysis and management of the world’s complexity from a socio-ecological perspective. The EAW is based on the fact that without the well-functioning biosphere there can be no society and without a society there can be no societal functions, including an economy. Fundamentally all wicked problems in the era of Anthropocene are global and have social and environmental backgrounds. A more holistic and multi-disciplinary systems thinking is needed to analyze and manage the causal complexity of the world in which we live. The EAW asks us to focus on post-material values because they are only loosely coupled with resource consumption. On the finite planet that is the question of what is enough and what is good for us. The EAW leads us maximizing psychological well-being and nurturing social harmony and cohesion. The EAW holds promise not only for solving social and ecological problems but also for helping people to be happier. It emphasizes human relationships and the meaningfulness of people’s unique lives. If people properly reflected on their values, especially what is ultimately good for those they care about, most of the wicked problems would be resolved.